ONLINE DIGITAL PLATFORMS DURING COVID-19 IN EFL CLASSES: VISUAL IMPAIRMENT STUDENT’ PERCEPTION - Sitti Maryam Hamid (ETERNAL (English, Teaching, Learning and Research Journal), 2020)
ABSTRACT. Due to the COVID-19 Pandemic, the government decided to implement work and learning from home. Teachers are expected to teach online. It also applied to teaching and learning English. Thus, Google Classroom, WhatsApp, and Zoom are commonly used as online learning platforms by EFL teachers and students during pandemic. The online digital platforms are also used as the main tool to provide teaching materials not only for the sighted student but also for Visual Impairment student (VIs). The present study is aimed at investigating how Visual Impairment student (VIs) perceive utilizing Digital Platforms in online learning, the barriers VIs faced in utilizing Digital Platforms, and the kinds of Digital Platforms that appropriate for Visual Impairment student (VIs). The study involved one Visual Impairment student (low vision) in one of the private universities of Makassar, South Sulawesi. Questionnaires and interviews were used to collect data. It analyzed using descriptive qualitative research.  The results of the study showed that Visual impairment has a positive response towards Google Classroom, WhatsApp, and Zoom in understanding the content, improving the ability to use various digital platforms in learning, presenting more interesting teaching materials, selecting of Digital Platforms by English Language skill, and hindering of utilizing Digital Platform. Even though slow-speed internet connectivity, take longer, and vague learning instruction was considered to be barriers in using Digital Platforms. Besides, Zoom is a digital platform that appropriates for VIs; Zoom is a video conferencing learning platform that offers VIs an opportunity to respond in real-time and there is a recording system that records the learning process from start to finish.